Inulin significantly improves serum magnesium levels in proton pump inhibitor‐induced hypomagnesaemia. Issue 11 (18th April 2016) - Hess, M. W.; de Baaij, J. H. F.; Broekman, M.; Bisseling, T. M.; Haarhuis, B.; Tan, A.; te Morsche, R.; Hoenderop, J. G. J.; Bindels, R. J. M.; Drenth, J. P. H.
Summary: Background: Proton pump inhibitors (PPI) are among the most widely prescribed drugs to treat gastric acid‐related disorders. PPI‐induced hypomagnesaemia, a defect in intestinal absorption of Mg 2+, can be a severe side effect of chronic PPI use. Aim: To restore serum Mg 2+ concentrations in PPI‐induced hypomagnesaemia patients by dietary supplementation with inulin fibres. Methods: Eleven patients with PPI‐induced hypomagnesaemia and 10 controls were treated with inulin (20 g/day). Each trial consisted of two cycles of 14‐day inulin treatment followed by a washout period of 14 days. Patients continued to use their PPI. Serum Mg 2+ levels served as the primary endpoint. Results: Inulin significantly enhanced serum Mg 2+ levels from 0.60 to 0.68 mmol/L in PPI‐induced hypomagnesaemia patients, and from 0.84 to 0.93 mmol/L in controls. As a consequence 24 h urinary Mg 2+ excretion was significantly increased in patients with PPI‐induced hypomagnesaemia (0.3–2.2 mmol/day). Symptoms related to hypomagnesaemia, including muscle cramps and paraesthesia, were reduced during intervention with inulin. Conclusion: Inulin increases serum Mg 2+ concentrations under PPI maintenance in patients with PPI‐induced hypomagnesaemia.